Implementation of Single Moving Average Methods For Sales Forecasting Of Bag In Convection Tas Loram Kulon - Dewi, Evita Noor Sofiana; Chamid, Ahmad Abdul (Jurnal Transformatika, 2019)
Convection Tas Loram Kulon is a Small and Medium Enterprises (UKM) located in the village of Loram Kulon, Jati District, Kudus Regency. The amount of effort makes everyone compete to be the best to get customers. When business owners cannot use information technology, a lot of information is wasted. Forms of manual reporting make it difficult for the owner to see the development of the business, as a result the owner can make mistakes in making decisions, especially for the addition or reduction of the stock. Forecasting is an estimate of the level of demand for one or more products over the coming periods. In forecasting the estimated level of demand in order to avoid excesses and not less inventory quantities based on past sales. Decision support investigated to predict the number of sales using the single moving average method. The Single Moving Average method uses a number of actual data requests to generate forecast values. The calculation is done by taking a group of values or data and then calculating the average and with the average used to calculate the next period forecast.
Keywords: Decision support system; single moving average; forecasting